Scattering Studies of Hydrophobic Monomers in Liposomal Bilayers: an Expanding Shell Model of Monomer Distribution - Richter, Andrew G. (2011)
Hydrophobic monomers partially phase-separate from saturated lipids when loaded into lipid bilayers in amounts exceeding 1:1 monomer:lipid molar ratio. This conclusion is based on agreement between two independent methods of examining the structure of monomer-loaded bilayers. Complete phase separation of monomers from lipids would result in increase in bilayer thickness and slight increase in the diameter of liposomes. Homogeneous distribution of monomers within the bilayer would not change the bilayer thickness and would lead to the increase in the liposome diameter. The increase in bilayer thickness, measured by the combination of small angle neutron scattering (SANS) and small angle X-ray scattering (SAXS), was approximately one half of what was predicted for complete phase separation. The increase in liposome diameter, measured by dynamic light scattering (DLS), was in the middle between values predicted for homogeneous distribution and complete phase separation. Combined SANS, SAXS, and DLS data suggest that at 1.2 monomer:lipid ratio, approximately one half of monomers are located in an interstitial layer sandwiched between lipid sheets. These results expand our understanding of using self-assembled bilayers as scaffolds for directed covalent assembly of organic nanomaterials. In particular, partial phase separation of monomers from lipids corroborates successful creation of nanometer-thin polymer materials with uniform imprinted nanopores. Pore-forming templates do not need to span the lipid bilayer to create a pore in the bilayer-templated films.